Islamic Education Leadership Management Model of Ibn Qayyim Al-Jauziyyah - Ifarida Wahyuningsih (Nalar Global Foundation, 2020)
This library research aimed to investigate the model of Islamic education leadership management according to Ibnu Qayyim al-Jauziyyah and its relevance to contemporer Islamic education in Indonesia. The data were collected from primary and secondary sources of literatures related to the research problem. Furthermore, the data were analyzed through several phases including data investigation, data designation, data reconstruction, data systematization, data reduction, data presentation, and conclusion. The results demonstrated that according to Ibnu Qayyim, Islamic education leadership management is the management that aims to preserve human’s natural disposition, to prevent them from committing wickedness, and to realize ubudiyah (total submission) to Allah. Islamic education leadership management proposed by Ibnu Qayyim is relefant to contemporer Islamic education in Indonesia because it is established based on Alquran that is able to adjust its relefeant to every time. In addition, education achievement is related to Manhaj (source of law) preservation and teachers’ competence.